2022
DOI: 10.1371/journal.pone.0267843
|View full text |Cite
|
Sign up to set email alerts
|

Influence of warm acupuncture on gut microbiota and metabolites in rats with insomnia induced by PCPA

Abstract: Background Insomnia is the most common of the sleep disorders. Current pharmacotherapy treatment options are usually associated with adverse effects and withdrawal phenomena. Therapeutic alternatives with a more favorable safety profile for patients are needed. Mongolian medical warm acupuncture (MMWA) is an emerging therapeutic option for treating insomnia. However, the underlying mechanisms responsible for the anti-insomnia efficacy of the MMWA remain unclear. This study aims to investigate the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The anti-insomnia effect of MMWA has been observed in rats with insomnia as MMWA treatment decreased ACh and NE levels and increased 5-HT and GABA levels in the serum. The gut microbiota improved, and cAMP and GABA transporter 1 (GAT-1) levels in the brain stem were reduced ( Yu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The anti-insomnia effect of MMWA has been observed in rats with insomnia as MMWA treatment decreased ACh and NE levels and increased 5-HT and GABA levels in the serum. The gut microbiota improved, and cAMP and GABA transporter 1 (GAT-1) levels in the brain stem were reduced ( Yu et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…[44] The results of Yu et al also suggested that warm acupuncture could regulate a variety of microbial genera and metabolites related to insomnia, including Blautia , reversing the butyrate-mediated upregulation of the cAMP signaling pathway and GAT-1 expression. [45] Collectively, this study is among the very few suggesting that SAAT could modulate the intestinal microbiota and serve as a measure to prevent inflammation and metabolism-associated diseases, whereas the mechanisms underlying SAAT regulating the intestinal microflora remain to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…[ 28 ] Studies have suggested that the warm acupuncture intervention could regulate a variety of microbial genera and metabolites related to insomnia. [ 29 ] Other studies have shown that warm acupuncture can improve brain neurotransmitters in people with insomnia. [ 30 ] Therefore, warm acupuncture may work indirectly by improving sleep, but the mechanism needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%